KIR and HLA-C interactions promote differential dendritic cell maturation and is a major determinant of graft failure following kidney transplantation. - Raj Hanvesakul; Chandrashekhar Kubal; Jason Moore; Desley Neil; Mark Cook; Simon Ball; David Briggs; Paul Moss; Paul Cockwell (PLoS ONE)
Background HLA-C is an important ligand for killer immunoglobulin like receptors (KIR) that regulate natural killer (NK) cell function. Based on KIR specificity HLA-C molecules are allocated into two groups, HLA-C1 or HLA-C2; HLA-C2 is more inhibiting to NK cell function than HLA-C1. We studied the clinical importance of HLA-C genotypes on the long-term graft survival of 760 kidney transplants performed at our centre utilising a population based genetic study and cell culture model to define putative mechanisms. Methods and findings Genotyping was performed using conventional DNA PCR techniques and correlations made to clinical outcomes. We found that transplant recipients with HLA-C2 had significantly better long-term graft survival than transplant recipients with HLA-C1 (66% versus 44% at 10 years, log-rank p = 0.002, HR = 1.51, 95%CI = 1.16-1.97). In in-vitro NK and dendritic cell (DC) co-culture model we made several key observations that correlated with the population based genetic study. We observed that donor derived NK cells, on activation with IL-15, promoted differential HLA-C genotype dependent DC maturation. In NK-DC co-culture, the possession of HLA-C2 by DC was associated with anti-inflammatory cytokine production (IL-1RA/IL-6), diminished DC maturation (CD86, HLA-DR), and absent CCR7 expression. Conversely, possession of HLA-C1 by DC was associated with pro-inflammatory cytokine synthesis (TNF-α, IL-12p40/p70), enhanced DC maturation and up-regulation of CCR7 expression. By immunohistochemistry the presence of donor NK cells was confirmed in pre-transplant kidneys. Conclusions We propose that after kidney transplantation IL-15 activated donor derived NK cells interact with recipient DC with less activation of indirect allo-reactivity in HLA-C2 positive recipients than HLA-C1 positive recipients; this has implications for long-term graft survival. Early events following kidney transplantation involving NK-DC interaction via KIR and HLA-C immune synapse may have a central role in long-term kidney transplant outcomes.